Effect of nitrogen sources on the growth of different species of Curvularia, Fusarium, Phoma and Botryodiplodia - S, Dandge V (Journal of Experimental Sciences, 2012)
Fruits and vegetables are eaten by man usually by uncooked methods so that several pathogenic organisms find their way into the human body. Fungal diseases play an important role in destruction of fruits and vegetables. The estimates reveal that losses due to plant diseases in India are over 200 crores of rupees annually. During the study greater frequency of Deuteromycetes was observed. The members of these species of Curvularia, Fusarium, Phoma and Botryodiplodia were the most dominant species among them. These fungi exhibit certain degree of specificity in their choice of food, but nitrogen substances are the most important substances required by them with regard to their vegetative and reproductive growth. The present studies deal with understanding the effect of thirteen nitrogen sources on species of Curvularia, Fusarium, Phoma and Botryodiplodia.